Theoretical and Experimental Study of Positive-Pressure Condensation Heat and Mass Transfer Processes in Bent-Tube Heat Exchangers - Jiaming Xing; Qing Cheng (Buildings)
Condensation dehumidification is currently the mainstream means of dehumidification, and the idea is to precipitate moisture by cooling the air below the dew point temperature; however, this process requires the use of a chiller to provide a low-temperature cooling source, which triggers reheat losses. By positive-pressure condensation, the dew point temperature can be increased, thereby increasing the cooling source temperature. In this paper, the dehumidification process in the bent-tube heat exchanger is investigated theoretically and experimentally. The bent-tube heat exchanger efficiently removes moisture from the air and increases the dehumidification efficiency through positive-pressure condensation. Experiments on positive-pressure condensation and dehumidification were conducted at varying pressures, with the results demonstrating that the model’s accuracy is within ±17%. As the fluid flow rate and pipe diameter rise, so do the dehumidification capacity and heat transfer coefficient. Furthermore, the findings show that the air humidity after dehumidification drops from 16.2 g/kg to 12.9 g/kg, meaning it is just over half of the value at atmospheric pressure, within the pressure that ranges from 100 kPa to 800 kPa. Increasing pressure enhances the heat transfer coefficient, while increasing humidity exacerbates this effect. With a 20% increase in wet air humidity, the heat transfer coefficient varies between 18% and 37%.